Optimizing Team Building Through Training for Karang Taruna Youth in Pasir Tanjung Village, Bogor - Medellu, Gita Irianda Rizkyani; Yudhistira, Santi; Maulana, Herdiyan; Mayangsari, Anggi; Agustian, Rayhan Alif; Rafif, Muhammad Rayendra; Alamsyah, Muhammad Iqbal (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
Pasirtanjung village has many young people who have an essential role in the village. However, although the number of youths is quite large, the Karang Taruna in Pasirtanjung Village is still unable to function optimally because members are not active enough to contribute. Therefore, Karang Taruna does not function like a youth organization. Meanwhile, to make the organization function optimally (achieve its goals), it is necessary to have contributions from each member. Community service activities are designed to build a better village community, in this case, Karang Taruna. This activity resulted in a program to improve team building for youth organizations. This is done to strengthen teamwork, improve group performance, and increase emotional attachment between group members and trust between members. Moreover, it optimizes the role of Karang Taruna in achieving its goal as one of the community institutions that helps build the village. The first step in building team building is strengthening group cohesiveness within the youth organization.A series of programs were designed to improve team building: 1) providing materials, 2) training, and 3) Focus group discussions. These team-building activities have been proven to help improve group performance. Systematic team-building activities can increase emotional attachment between group members and trust between members. This series of activities can ultimately be measured through pretest-posttest measurements related to group cohesion. The results show that the understanding of youth regarding group cohesion in youth organizations has increased after being given training. This training can provide new insights to the trainees that developing an organization requires an active and mutually supportive team.